A Systematic Review of Opioid Use Disorder and Related Biomarkers - Bryant, Bianca M.; Eaton, Ellen; Li, Li (Frontiers in Psychiatry, 2021)
The objective of this systematic review is to examine the relationship between opioid use disorder (OUD) and its related biomarkers, as well as the effects of pharmacotherapy for OUD on biomarkers. The eligibility criteria are the inclusion of human population studies focusing on biomarkers, including the immune system, related to OUD or opioid-related disorders. English, peer reviewed, original research, case studies or case series, and clinical trials were included in this review. Papers were excluded if they met one or more of the following criteria: animal studies, review articles, studies focusing only on OUD or opioid-related disorders without mention of potential biomarkers, studies focusing only on biomarkers and/or the immune system without relating to OUD or opioid-related disorders, and studies that focused on other substance use disorders other than OUD specifically. A PubMed, PsycINFO, and Cochrane databases search on August 25, 2020, yielded 101 results; only 14 articles met inclusion criteria that were included in this review. However, heterogeneity of study definitions and measurements should be noted. Various potential biomarkers indicated systemic, peripheral, and chronic inflammation in patients with OUD or opioid-related disorders. Medications, including buprenorphine and methadone, significantly decreased chronic inflammation in this population. Our results suggest that patients with OUD or opioid-related disorders have potential biomarkers that can be targeted to provide optimal treatment options for this population. A better understanding of potential biomarkers may assist to identify at-risk populations, monitor disease progression and treatment response, and develop therapeutic strategies for OUD.